(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted at farmers’ field of Charfashion upazila in Bhola district under AEZ-18 during the Rabi season of 2015-2016 and 2016-2017 to find out suitable soil salinity management practice(s) for maximizing potato yield as well as farmers’ income. Two planting systems viz. raised bed and flat land, and four management systems with fertilizers and mulching were considered in a factorial experiment. The rate of increase in soil salinity in raised beds was significantly lower than that of flat land. On an average, raised bed planting produced 13.04% higher tuber yield than flat land planting. The combination of raised bed + recommended fertilizer (RF) with cowdung @ 5 t ha-1 as IPNS+ straw mulch (@ 3.5 t ha-1) produced the highest tuber yield in both the years (average 21.66 t ha-1) and it was 75.10% higher than flat planting system with no mulch. This treatment combination also provided the highest average gross margin (Tk. 115945 ha-1) and BCR (2.26). Besides, combination of raised bed + RF+25% K+ straw mulch provided average tuber yield (20.91 t ha-1), gross margin (Tk. 110969 ha-1) and BCR (2.25), which were very close to above treatment combination. The lowest average potato yield (12.51 t ha-1), gross margin (Tk. 39835 ha-1) and BCR (1.50) were obtained from combination of flat land planting + RF +no mulching. So, combination of raised bed + mulching+ RF along with IPNS basis cowdung @ 5 tha-1 or 25% extra K can help minimize soil salinity and produce significantly higher potato yield in the coastal areas. Bangladesh J. Agril. Res. 43(4): 655-668, December 2018